882 1/2 amazing answers to your questions about the Titanic - Brewster, Hugh.; Coulter, Laurie; Marschall, Ken (New York : Scholastic, 1998)
Questions and answers present information about the building, passengers, launching, sailing, sinking, and rediscovery of the Titanic. Includes illustrations, archival images, and step-by-step diagrams.
Keywords: Titanic (Steamship) -- Miscellanea -- Juvenile literature; Titanic (Steamship) -- Miscellanea; Shipwrecks -- North Atlantic Ocean -- Miscellanea -- Juvenile literature..; Shipwrecks -- Miscellanea; Questions and answers